Literature Review on The Influence of Institutional Ownership and Board Diversity Gender (BDG) on Company Performance - Yulista, Enggar Rahma; Kusumaningtias , Rohmawati (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study highlights the influence of institutional ownership and gender diversity on the board of directors on company performance. This research is a qualitative study using a literature review method. The literature reviewed includes articles from international and national journals, totaling 20 articles from 2019 to 2025. This study highlights the influence of institutional ownership and gender diversity on the board of directors on company performance. Institutional ownership has been shown to improve corporate oversight and governance, thereby strengthening operational efficiency and long-term stability, in line with agency and stakeholder theories. Meanwhile, gender diversity adds multiple perspectives to decision-making, improves oversight, and supports sustainability practices through more transparent ESG reporting. These two factors work synergistically to build an inclusive and effective management structure that not only encourages innovation and risk management but also maintains a balance between internal and external interests. The results of the study show that the combination of these two factors contributes positively to improving overall and sustainable company performance, while strengthening the company’s position in facing global competition and social and environmental sustainability demands. Institutional ownership has been shown to improve corporate oversight and governance, thereby strengthening operational efficiency and long-term stability, in line with agency and stakeholder theories. Meanwhile, gender diversity adds multiple perspectives to decision-making, improves oversight, and supports sustainability practices through more transparent ESG reporting. These two factors work synergistically to build an inclusive and effective management structure that not only encourages innovation and risk management but also maintains a balance between internal and external interests. The results of the study show that the combination of these two factors contributes positively to improving overall and sustainable company performance, while strengthening the company’s position in facing global competition and social and environmental sustainability demands